Diseño de biodigestor a partir de porcinaza (2022)
The purpose of this document is the conceptual design of a biodigester from pig manure, for the production of biogas and biofertilizer, as an added value to small farms with pork producers. For the development of the biodigester, the pig manure from two farms in the municipality of Pacho, Cundinamarca, is characterized. Where one of them has a focus on raising pigs, while the other farm has a focus on fattening pigs. This characterization is done with physicochemical and microbiological tests, these tests are done under the standard methods for wastewater analysis.